1992
DOI: 10.1089/lps.1992.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Impairment During Laparoscopic Cholecystectomy in a Patient with a Ventriculoperitoneal Shunt

Abstract: A patient with a recently placed ventriculoperitoneal shunt suffered ventilatory impairment due to decreased thoracic compliance related to massive subcutaneous emphysema during laparoscopic cholecystectomy. The patient recovered uneventfully; however, recently established closed communication between the peritoneal cavity and the subcutaneous space may be a relative contraindication to laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…While specific details about all the shunts used were not available, the operative reports did note that the valves were tested at the time of shunt placement. It has been reported that laparoscopic procedures performed in patients within 10 days of VP shunt placement may result in massive subcutaneous emphysema [5]. The insufflated CO 2 travels along the peritoneosubcutaneous tracts.…”
Section: Discussionmentioning
confidence: 99%
“…While specific details about all the shunts used were not available, the operative reports did note that the valves were tested at the time of shunt placement. It has been reported that laparoscopic procedures performed in patients within 10 days of VP shunt placement may result in massive subcutaneous emphysema [5]. The insufflated CO 2 travels along the peritoneosubcutaneous tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory complications after laparoscopic surgery are significantly lower than open surgery (Rose, 1992;Rothwell et al, 1992;Schwed et al, 1992). Positioning and intra peritoneal pressures raise alveolar death space; witch can be already increased by diseases like in obstructive bronchopneumonia.…”
Section: Respiratory Diseasementioning
confidence: 99%
“…The leakage tests of these valves are not totally reliable when they are suspended in cephaloraquideum liquid. A diffusion of carbon dioxide occurs along the subcutaneous way of the valve (Schwed et al, 1992).Cerebral and retinal vascular accidents can occur.…”
Section: Intracraneal Hypertensionmentioning
confidence: 99%
“…The first reported case of laparoscopic surgery in a patient with VPS appears to have been by Schwed et al [4]. Li et al performed a retrospective review of 26 patient charts for a total of 39 operative procedures between 1995 and 2003.…”
Section: Discussionmentioning
confidence: 99%